Endoscopic ultrasound-guided fine needle aspiration of pancreatic masses: the utility and impact on management of patients - Kliment, Martin; Urban, Ondrej; Cegan, Martin; Fojtik, Petr; Falt, Premysl; Dvorackova, Jana; Lovecek, Martin; Straka, Martin; Jaluvka, Frantisek (Scandinavian journal of gastroenterology, 2010)
OBJECTIVE: It is controversial whether endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is beneficial in all patients with suspected pancreatic cancer. The aim of this study was to assess diagnostic yield, safety and impact of EUS-FNA on management of patients with solid pancreatic mass. MATERIAL AND METHODS: Consecutive patients undergoing EUS-FNA of solid pancreatic mass were enrolled. Gold standard for final diagnosis included histology from surgical resection. In patients without surgery, clinical evaluation methods and repeated imaging studies were used for the comparison of initial cytology and final diagnosis. Patients were followed-up prospectively focusing on subsequent treatment. RESULTS: Among 207 enrolled patients, final diagnosis was malignant in 163 (78.6%) and benign in 44 (21.4%). The sensitivity, specificity and accuracy of EUS-FNA in diagnosing pancreatic cancer were 92.6% (95% CI: 87.20-95.96), 88.6% (95% CI: 74.64-95.64) and 91.8% (95% CI: 87.24-94.81), respectively. No major and five (2.4%) minor complications occurred. Of 151 true-positive patients by EUS-FNA, 57 (37.7%) were surgically explored, of whom 28 (49.1%) underwent resection. Ten of 12 patients with false-negative cytology were explored based on detection of mass on EUS, of whom two had a delay due to false-negative cytology without curative treatment. From the whole study cohort, EUS-FNA had positive and negative impacts on subsequent management in 136 (65.7%) and 2 (0.9%) patients, respectively. CONCLUSIONS: EUS-FNA provides accurate diagnosis in 92% and has positive therapeutic impact in two-thirds of patients with solid pancreatic mass. Despite negative cytology, surgical exploration is recommended in clinical suspicion for pancreatic cancer and solid mass on EUS.
Keywords: ROC Curve; Pancreatectomy; endosonografie; pankreatektomie; nádory slinivky břišní; Humans; lidé středního věku; Female; Aged; dospělí; senioři; lidé; reprodukovatelnost výsledků; Endosonography; Adult; Follow-Up Studies; ženské pohlaví; Male; Pancreatic Neoplasms; Middle Aged; Reproducibility of Results; Aged, 80 and over; senioři nad 80 let; Biopsy, Fine-Needle; ROC křivka; mužské pohlaví; tenkojehlová biopsie; prospektivní studie; následné studie; Prospective Studies